Synthesis, Molecular Docking, and Antimicrobial Evaluation of 2-(Substituted Amino)-N-(6-Substituted-1,3-Benzothiazol-2yl) Acetamide - Pawar, Smita; Kale, Amol; Zori, Priya; Zope, Dhanashri (Current Drug Discovery Technologies, 2025)
BackgroundThe development of antimicrobial agents is crucial for several reasons, primarily to combat infectious diseases and to address the growing threat of antimicrobial resistance. The need for the continued development of antimicrobial drugs persists despite the presence of many existing drugs for several reasons, viz emerging new pathogens and diseases, resistance to existing drugs, and propagation of multidrug resistance to existing drugs.ObjectiveThe objective of the study was to synthesize and evaluate the antimicrobial potential of newly synthesized benzothiazole derivatives.MethodsA new series of 2-(substituted amino)-N-(6-substituted-1,3-benzothiazol-2yl)acetamide BTC(a-t) has been synthesized by reacting it with chloracetyl chloride with substituted 2-amino benzothiazole and further refluxed with various substituted amines to obtain target compounds. The synthesized compounds were screened experimentally for their antimicrobial property against gram-positive and gram-negative bacteria and fungi. The zone of inhibition and minimum inhibitory concentration of compounds were determined against selected bacterial and fungal strains. Further docking study was carried out to check the probable interactions with the selected protein using V-life MDS 3.5 software (DNA gyrase, PDB: 3G75).ResultsCompounds BTC-j N-(6-methoxy-1,3-benzothiazol-2-yl)-2-(pyridine-3-ylamino)acetamide and BTC-r N-(6-nitro-1,3-benzothiazol-2-yl)-2-(pyridine-3-ylamino)acetamide were found to have good antimicrobial potential. The compound BTC-j showed good antibacterial activity against S. aureus at an MIC value of 12.5 µg/mL, B. subtilis at MIC of 6.25µg/mL, E. coli at MIC of 3.125µg/mL, and P. aeruginosa at MIC of 6.25µg/mL. Thus, from the result, it was observed that compounds BTC-j, BTC-f, BTC-n, and BTC-r exhibited significant antibacterial and antifungal potential at different concentrations.ConclusionThe present study resulted in the successful synthesis of 2-acetamido substituted benzothiazole derivatives BTC(a-t) with good yields. The dock score of the compounds and the antimicrobial activity were found to be consistent. No statistical difference in the antimicrobial activity of the standard and test compounds was found, indicating that the test compounds have comparable activity. Therefore, benzothiazole linked to heterocyclic rings with an acetamide linkage may serve as promising lead molecules for further optimization in the journey to discover potent antibacterial agents. Thus, we conclude that the synthesized compounds have the potential for further development as novel antimicrobial agents.
Keywords: antimicrobial